Heart rate response during a session with different active videogames. - Brito-Gomes, Jorge Luiz; Perrier-Melo, Raphael José; Albuquerque, Fabíola Lima de; Costa, Manoel da Cunha (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Due to technological advancement, children and young adults pass to watching television, using the computer and playing videogames more frequently, favoring physical inactivity. However, a new form of videogames comes up as a possible tool for promoting physical activity. Objective: To examine changes in heart rate in a session with different sets of active videogames (Xbox360 with Kinect) and verified the intensities affected by the percentage of maximum heart rate. Method: 8 young adults (21 ± 1.60 years, 22 ± 1.60 kg / m²) with no gaming experience, performed on the Moment 1 anthropometric measurements (weight, height), hemodynamic measurements (heart rate at rest) and measurement of oxygen consumption. At Moment 2, a session with 4 different games Kinect Sports (modalities: Boxing, Table Tennis and Volleyball) and Dance Central 3. The session lasted 72 minutes (3 min each game familiarization then played for 10 minutes and then performed a passive rest 5 minutes). Throughout the session was monitored every minute heart rate. Results: There was significant increase in heart rate at different moments during the game, reaching reached 121 bpm ± 7.99, 121 ± 6.01 bpm, 113 bpm ± 3.95, 103 ± 4.16 bpm for Kinect Sports: Boxing, Dance Central 3, Kinect Sports Volleyball and Table Tennis respectively. Discussion: The games Dance Central 3 and Kinect Sports: boxing and volleyball reached moderate intensity at different times. However, the Kinect Table Tennis game showed few significant elevations. Besides presenting moments of analysis in the intensity, range considered light. Conclusion: The games analyzed caused significant increases in heart rate, reaching levels of light to moderate.